Why carers of people with dementia do not utilise out‐of‐home respite services. (18th March 2013) - Phillipson, Lyn; Magee, Christopher; Jones, Sandra C.
Abstract While many people with dementia require institutional care, having a co‐resident carer improves the likelihood that people can live at home. Although caregiving can have positive aspects, carers still report a high need for respite. Despite this need, the use of respite services for carers of people with dementia is often low. This article investigates carer beliefs regarding out‐of‐home respite services and why some carers do not utilise them. A total of 152/294 (51.7%) carers of community‐dwelling people with dementia (NSW, Australia) who were sent a survey completed it (November 2009–January 2010). Despite reporting unmet need for both services, 44.2% of those surveyed were not utilising day respite and 60.2% were not utilising residential respite programmes. Binary logistic regression models were used to examine factors associated with non‐use using the Theory of Planned Behaviour within an expanded Andersen Behavioural Model on a final sample of 113 (due to missing data). The model explained 66.9% of the variation for day centres, and 42% for residential respite services. Beliefs that service use would result in negative outcomes for the care recipient were strongly associated with non‐use of both day care [OR 13.11; 95% CI (3.75, 45.89)] and residential respite care [OR 6.13; 95% CI (2.02, 18.70)] and were more strongly associated with service non‐use than other predisposing, impeding and need variables. For some carers who used services despite negative outcome beliefs, the benefits of respite service use may also be diminished. To improve use of out‐of‐home respite services in this vulnerable group, service beliefs should be addressed through service development and promotion that emphasises benefits for both carer and care recipients. Future research utilising behavioural service models may also be improved via the inclusion of service beliefs in the study of health and social service use.